Crop rotation. XVII. Effects an grain yield and root diseases of wheat from 1980 to 1987 - Santos, Henrique Pereira dos; Reis, Erlei Melo; Pereira, Luiz Ricardo (Pesquisa Agropecuaria Brasileira, 2014)
Between 1980 and 1987, at the National Wheat Research Center (CNPT-EMBRAPA), Passo Fundo, RS, Brazil, the effect of crop rotation Systems on wheat yield, root disease severity, yield components and other agronomic characteristics of wheat planta were assessed. Four rotation systems were used for wheat: 1) monoculture; 2) rapeseed, barley, lupins or serradella and wheat rotation; 3) trefoil, trefoil or oats, common wetch and wheat rotation; 4) rapeseed, flax, lupines or serradella and wheat rotation. Winter crops were conventionally seeded. The experimental design was complete randomized blocks with four replications. Experimental plots had an area of 120 m2. Wheat cultivated after: a) rapeseed, flax and lupines or 2) after legumes or c) after rapeseed, barley and lupines yielded more than under monoculture. Root diseases severity was higher under monoculture and decreased under rotation. Increments in 1.000 kernels weight were responsible for the higher wheat yield observed under rotation system than under monoculture. Wheat grain yields decreased linearly with an increase in root diseases severity.